Public employment reforms in Colombia under the 1991 Constitution framework - Saavedra Echeverry, Saúl; ESAP, Valle del Cauca, Cali. (Pontificia Universidad Javeriana, 2015)
After more than two decades of institutional reforms in public employment introduced by relevant actors in the Colombian political system, the result has been the creation of a network of formal rules with different and opposite properties: it is a stratified system of public employment subject to the contradictions generated by the logical disparity accompanying three orientations of public personnel. Under these conditions the ambiguity is the outstanding feature of the institutions’ staff and political factorthat generate higher costs to stakeholders in public administration installed in the Colombian civil service system merit as mandated by the Constitution in 1991.